Functional evaluation of various modalities of management in floating knee injuries at a tertiary care centre in central India - Sharma, D. K.; Banodha, Laxman; Mahajan, Pranav; Meena, Anshul; Goyal, Roshan (International Journal of Research in Orthopaedics, 2023)
Background: The injuries involving femur and tibia fractures due to high velocity are known as floating knee injuries. These fractures may involve the shaft, metaphysis or the articular surface. There are many complications associated with these injuries. This study evaluates the functional, clinical and radiological outcomes of floating knee injuries. Methods: A Prospective and interventional study was performed at MGMMC and MYH Hospital, Indore. We included 30 patients in our study. Femur fractures are managed by intramedullary nailing or distal femur plating. Tibia fractures are managed by Intramedullary nailing or tibia plating. Patient were called for regular follow up for a minimum of 6 months. Functional and clinical evaluation done by Karlstorm and olerud scoring system and radiological outcome by union on x rays were done. Results: Out of 30 patients 28 (93.33%) male and 2 (6.66%) female. According to Fraser classification, 17 (56.66%) type 1, 4 (13.33%) type 2A, 4 (13.33%) type2B, 5 (16.66%) type 2C injuries. A majority of the injuries occurred due to road traffic accidents involving right limb 21 (70%) more then left 9 (30%). Knee stiffness occurred in 8, infection in femur 3, infection in tibia 2, malunion of femur 2, limb length discrepancy in 2 patients. Outcome was excellent in 5 (16.66%), Good in 10 (33.33%), Acceptable in 9 (30%) and poor in 6 (20%). Conclusions: Fraser type 1 fracture has excellent results and Fraser type 2C has poor results. Closed fracture has better outcome compared to compound Fractures. A better functional outcome can be determined on the basis of implant choice based on Fraser Classification, level of injury, open or closed injury, simple or compound type of fracture.